2021
DOI: 10.3390/nu13072463
|View full text |Cite
|
Sign up to set email alerts
|

Daily Rhythm of Fractal Cardiac Dynamics Links to Weight Loss Resistance: Interaction with CLOCK 3111T/C Genetic Variant

Abstract: The effectiveness of weight loss treatment displays dramatic inter-individual variabilities, even with well-controlled energy intake/expenditure. This study aimed to determine the association between daily rhythms of cardiac autonomic control and weight loss efficiency and to explore the potential relevance to weight loss resistance in humans carrying the genetic variant C at CLOCK 3111T/C. A total of 39 overweight/obese Caucasian women (20 CLOCK 3111C carriers and 19 non-carriers) completed a behaviour–dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…A single nucleotide polymorphism entitled 3111 T/C (rs1801260) (Thymine to Cytosine nucleotide substitution Position 3111 of DNA sequence) was detected in the 3'-flanking region in the human CLOCK gene [ 9 ]. A previous study showed that people who are heterozygous or homozygous for the 3111 C allele have been reported to be more likely the evening preference and obese than those with the TT genotype [ 10 , 11 , 12 ]. Food is one of the external synchronizers of our environmental clocks.…”
Section: Introductionmentioning
confidence: 99%
“…A single nucleotide polymorphism entitled 3111 T/C (rs1801260) (Thymine to Cytosine nucleotide substitution Position 3111 of DNA sequence) was detected in the 3'-flanking region in the human CLOCK gene [ 9 ]. A previous study showed that people who are heterozygous or homozygous for the 3111 C allele have been reported to be more likely the evening preference and obese than those with the TT genotype [ 10 , 11 , 12 ]. Food is one of the external synchronizers of our environmental clocks.…”
Section: Introductionmentioning
confidence: 99%